Tradition Multicultural Society Religion in Serang City - Rt Bai Rohimah; Achmad Hufad; Suroso Mukti Leksono (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2022)
This article examines the characteristics and cultural identity, as well as the socio-religious rituals of the people of Serang city. The research used is anthropological ethnography method. In analyzing the data, the researcher used a functional-structural approach. The results showed that although the people in Serang city were categorized as multicultural society, they still carried out their religious traditions. There are several things that affect this harmony, including the factor of religious understanding of each individual, educational background and social relations of the community. For the residents of Serang city, the distinctive characteristics wrapped in tradition have a positive meaning as local wisdom and have religious values ​​that are still maintained today. Keywords: Local Belief, Multicultural, Modern, Tradition .